2009
DOI: 10.1098/rspb.2008.1530
|View full text |Cite
|
Sign up to set email alerts
|

The double odyssey of Madagascan polystome flatworms leads to new insights on the origins of their amphibian hosts

Abstract: Polystomatid flatworms are parasites of high host specificity, which mainly infect amphibian hosts. Only one polystome species has so far been recorded from Madagascar despite the high species richness and endemicity of amphibians on this island. Out of the 86 screened Malagasy frog species, we recovered polystomes from 25 in the families Ptychadenidae and Mantellidae. Molecular phylogenetic analysis uncovered an unexpected diversity of polystome species belonging to two separate clades: one forming a lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…Furthermore, molecular studies with greater taxonomic coverage have particularly focused on biomedically or economically important taxa such as Schistosomatidae (Lockyer et al, 2003b;Orélis-Ribeiro et al, 2014) or particular lineages with a high host specificity such as Polystomatidae (Bentz et al, 2001(Bentz et al, , 2006Badets et al, 2011Badets et al, , 2013Héritier et al, 2015). To better Figure 6 Ultrametric tree of neobatrachian polystomes inferred from MULTIDIVTIME (Modified after Verneau et al (2009b).). Calibration points (black rectangles, nodes 1e3) were deduced from historical biogeographical scenarios suggested by Bentz et al (2001Bentz et al ( , 2006 and Badets et al (2011).…”
Section: Molecular Clock Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, molecular studies with greater taxonomic coverage have particularly focused on biomedically or economically important taxa such as Schistosomatidae (Lockyer et al, 2003b;Orélis-Ribeiro et al, 2014) or particular lineages with a high host specificity such as Polystomatidae (Bentz et al, 2001(Bentz et al, , 2006Badets et al, 2011Badets et al, , 2013Héritier et al, 2015). To better Figure 6 Ultrametric tree of neobatrachian polystomes inferred from MULTIDIVTIME (Modified after Verneau et al (2009b).). Calibration points (black rectangles, nodes 1e3) were deduced from historical biogeographical scenarios suggested by Bentz et al (2001Bentz et al ( , 2006 and Badets et al (2011).…”
Section: Molecular Clock Studiesmentioning
confidence: 99%
“…Finally, the root prior was set at 160 Ma (sd AE 5 Myr), corresponding to an initial divergence separating Asian and Australian polystomes from all other neobatrachian polystomes (Badets et al, 2011), hypothetically corresponding to a separation of the western and eastern components of Gondwanaland. Divergence time estimates (see Verneau et al, 2009b) are reported for two nodes that are relevant for understanding the origin of the new Malagasy genus, i.e. Madapolystoma (see Du Preez et al, 2010).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Amplification for each molecular marker was done according to the Oliva et al: Parapedocotylinae, new subfamily of Diclidophoridae protocols described by Chisholm et al (2001), Hall et al (1999) and Verneau et al (2009) for the 28S rDNA, 18S rDNA gene and cox1 gene, respectively. Double-stranded PCR products were cleaned using an E.Z.N.A.…”
Section: Methodsmentioning
confidence: 99%
“…The 18S rRNA gene was amplified with forward primer Sb3a (5'-GGAGGGCAAGTCT-GGTGC-3') and the reverse primer A27a (5'-CCATACAAAT-GCCCCCGTCTG-3') following the protocol described by Hall et al (1999). The cox1 gene was amplified with forward L-CO1 (5'-TTTTTTGGGCATCCTGAGGTTTAT-3') and the reverse primer H-CO1 (5'-TAAAGAAAGAACATAATGAAAATG-3') (Verneau et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Thus it is necessary to survey parasite assemblages in environments with different levels of anthropogenic influence . Indeed, there have been recent parasitological surveys on Malagasy frogs on monogeneans (Verneau et al, 2009;Du Preez et al, 2010;Raharivololoniaina et al, 2011;Berthier et al, 2014), mites (Wohltmann et al, 2007) and protists (Delvinquier et al, 1998), while nematodes were surveyed broadly in 1950s and 1960s (Chabaud Brygoo 1957, 1958Chabaud et al, 1961, although see recent information in Kuzmin et al, 2013).…”
mentioning
confidence: 99%